2015
DOI: 10.1002/ejic.201403115
|View full text |Cite
|
Sign up to set email alerts
|

Intercalative Ion‐Exchange Route to Amino Acid Layered Double Hydroxide Nanohybrids and Their Sorption Properties

Abstract: A soft chemical route to amino acid layered double hydroxide (LDH) nanohybrids was demonstrated on the basis of an intercalative ion-exchange reaction. Two different amino acids, phenylalanine and glutamic acid, were intercalated and stabilized in the interlayer space of a 2-dimensional double hydroxide lattice by electrostatic interaction. An attempt was also made to understand the effect of the intracrystalline structure of the amino acid in the LDH on the specific surface area, porosity, and gas sorption pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Moreover, the interlayer anions (A m− ) in LDHs can be replaced with various anions (A m− =Cl − , NO 3 − , CO 3 2− , SO 4 2− , organic or bioactive molecules, and etc.) depending upon the chemicals for synthesis or the biofunctional molecules to be coprecipitated, such as vitamins,, amino acids,, anticancer drugs, anti‐inflammatory drugs,, antibiotics,, and nucleotides including DNAs and RNAs, due to the anionic exchange property.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the interlayer anions (A m− ) in LDHs can be replaced with various anions (A m− =Cl − , NO 3 − , CO 3 2− , SO 4 2− , organic or bioactive molecules, and etc.) depending upon the chemicals for synthesis or the biofunctional molecules to be coprecipitated, such as vitamins,, amino acids,, anticancer drugs, anti‐inflammatory drugs,, antibiotics,, and nucleotides including DNAs and RNAs, due to the anionic exchange property.…”
Section: Introductionmentioning
confidence: 99%
“…Among the methods generally applied for this purpose [43] one can find wet chemical as well as mechanochemical techniques. The wet chemical methods can be direct anion exchange from water [44], aqueous ethanol or acetone [45]; co-precipitation of the components including the anion to be intercalated [46]; the dehydration-rehydration method of intercalation [47,48]. Occasionally, ultrasonic treatment increases the efficiency of the anion exchange or allows the introduction of anions, which would be difficult without its use [49,50].…”
Section: Wet Chemical Methodsmentioning
confidence: 99%
“…It can be concluded that the LDH host could be protecting the DNA bio‐molecules from their degradation and transport to exact target sites within the human body. Furthermore, anionic active drugs are also successfully intercalated into various LDH host families and the purpose of the active species is to regulate the viability of using these intercalated nanohybrids as carriers for transport, storage, and eventually for the control release of active molecules …”
Section: Intercalation Chemistrymentioning
confidence: 99%